Iodine and quality of life: elimination of the deficiency of iodine in Peru - Rosales Mayor, Edmundo (2018)
Introduction: Daytime somnolence and poor sleep quality have been described in medical students during their hospital-based practical sessions, and we do not know the occurrence of these situations during holidays.Objective: To explore the differences in daytime somnolence, sleep quality, and sleeping habits in medical students during the hospital-based practical sessions period, and during holidays.Material and method: A case series with a single group that was assessed in two periods. A non-probabilistic sample comprising 6th year medical students was used. Epworth Somnolence Scale (ESS) and Pittsburgh Sleep Quality Index (PSQI) were administered to the study subjects two weeks before finishing their period of hospital based practical sessions, and two weeks after this period had finished (during holidays).Results: 76 (72%) 6th year medical students participated during the hospital-based practical sessions period and 82 (78%) did during holidays. There were no differences between the two groups with respect to age and gender. There was a statistically significant difference between both periods (practical sessions vs. holidays) in the scores for the two scales used: ESS (9,88 vs. 8,27; p= 0,015) and PSQI (6,53 vs. 5,55; p= 0,022). When comparing the practical sessions period against holidays, we found reductions in the percentage of persons with bad sleep quality (59% vs. 43%; p= 0.040), in persons with excessive daytime somnolence (39% vs. 26%; p= 0,086), in sleeping less than 6 hours (68% vs. 46%; p= 0.006), in a subjective <85% sleep efficiency (59% vs. 22%, p<0.001), and an increase in the number of sleeping hours reported (5,97 h vs. 6,53 h; p= 0,005) during holidays.Conclusions: Medical students had poor sleep quality and more daytime somnolence during their hospital based practical sessions period. Their scores improved during holidays, but the difference did not reach statistical significance when comparing daytime somnolence. It was observed in both periods that the scores for the two scales administered (ESS and PSQI) were abnormal. It is necessary to implement studies for assessing the effect of such alterations in their academic and working performance, and for knowing the reasons why poor sleep quality and daytime somnolence persist during holidays.